Effectiveness of pain and symptom management training for paediatric clinicians. (August 2017) - Chen, Yong-Chuan; Peng, Niang-Huei; Chen, Chao-Huei; Lu, Frank Leigh; Chang, Yue-Cune; Liu, Hsin-Li; Yeats, Mark
Pain and symptom management is the most important area of paediatric palliative care, but clinicians often receive little training in this area. Our research evaluated the effectiveness of pain and symptom management training among paediatric professionals. A quasi-experimental pretest–posttest study was used. Fifty-three paediatric nurses and 18 paediatricians participated in this study for a response rate of 80%. Results showed significant main effects of training on confidence levels ( p < 0.001), and attitude scores ( p < 0.001) among paediatric clinicians in a variety of areas, with no differences in scores between paediatricians and nurses. This suggests that education can effectively increase paediatric clinicians' confidence in and attitudes towards providing pain and symptom management for children with severe illness. Further training is needed to promote interdisciplinary healthcare team work to improve the effectiveness of pain and symptom management.